Lung ultrasound score to predict development of acute chest syndrome in children with sickle cell disease - Pedro P.M.G. Vieira; Josefina A.P. Braga; Rodrigo Regacini (Hematology, Transfusion and Cell Therapy)
Objective: This study aims to identify lung ultrasound (LUS) findings associated with acute chest syndrome (ACS) at the time of admission and 24–48 h later, to compare these to chest radiography (CXR) findings and to establish a score to predict the development of this pulmonary complication in sickle cell disease (SCD) children Methods: A prospective observational study of SCD children presenting signs or symptoms of ACS evaluated by LUS and CXR at admission and 24–48 h later. A score was conceived to predict the evolution of ACS during hospitalization based on ultrasonographic findings. Results: Seventy-eight children were evaluated; 61 (78.2 %) developed ACS. A score greater than one at admission showed sensitivity, specificity, accuracy, and positive predictive value (PPV) of 75.4 %, 88.2 %, 78.2 %, and 95.8 %, respectively to predict ACS, while only 32 (52.5 %) CXR showed alterations. The development of ACS during hospitalization was unlikely for a score of zero and very likely for a score greater than one at admission. Regarding follow-up exams, a score greater than one showed sensitivity, specificity, accuracy, and PPV of 98.4 %, 76.5 %, 93.6 %, and 92.8 %, respectively to predict the development of ACS. ACS development was very unlikely for a score of zero and very likely for a score greater than zero in the follow-up. Conclusion: LUS is an effective tool to assess risk for the development of ACS in SCD children with clinical suspicion.